'Trophic whales' as biotic buffers: weak interactions stabilize ecosystems against nutrient enrichment. (29th December 2014) - Schwarzmüller, Florian; Eisenhauer, Nico; Brose, Ulrich
Summary: Human activities may compromise biodiversity if external stressors such as nutrient enrichment endanger overall network stability by inducing unstable dynamics. However, some ecosystems maintain relatively high diversity levels despite experiencing continuing disturbances. This indicates that some intrinsic properties prevent unstable dynamics and resulting extinctions. Identifying these 'ecosystem buffers' is crucial for our understanding of the stability of ecosystems and an important tool for environmental and conservation biologists. In this vein, weak interactions have been suggested as stabilizing elements of complex systems, but their relevance has rarely been tested experimentally. Here, using network and allometric theory, we present a novel concept for a priori identification of species that buffer against externally induced instability of increased population oscillations via weak interactions. We tested our model in a microcosm experiment using a soil food‐web motif. Our results show that large‐bodied species feeding at the food web's base, so called 'trophic whales', can buffer ecosystems against unstable dynamics induced by nutrient enrichment. Similar to the functionality of chemical or mechanical buffers, they serve as 'biotic buffers' that take up stressor effects and thus protect fragile systems from instability. We discuss trophic whales as common functional building blocks across ecosystems. Considering increasing stressor effects under anthropogenic global change, conservation of these network‐intrinsic biotic buffers may help maintain the stability and diversity of natural ecosystems. Abstract : Natural ecosystems inherit structural components that buffer against external stressors such as nutrient enrichment. In this study, the authors provide methods for a‐priori identification of one class of structural important species, the 'trophic whales'. They examine their role in exemplary model analyses and test the concept empirically in a microcosm experiment.